2019
DOI: 10.3389/fpsyg.2019.02908
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Therapy for Depression: A 3-Year Follow-Up Study Assessing Recovery, Relapse, Work Force Participation, and Quality of Life

Abstract: A major challenge in the treatment of depression has been high relapse rates following treatment. The current study reports results from a 3-year follow-up of patients treated with metacognitive therapy (MCT). Thirty-four of the 39 patients enrolled in the original study attended assessment (participation rate of 87%). There were large reductions in symptoms of depression, anxiety, interpersonal problems, and worry, as well as metacognitive beliefs. Three patients fulfilled diagnostic criteria for axis-I disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
2
25
0
3
Order By: Relevance
“…Our results are in accordance with others demonstrating the clinical efficacy of MCT [ 2 , 6 , 16 , 22 ]. A recent meta-analysis integrating data of 15 trials demonstrated large effect sizes of MCT against waitlist condition (Hedges’ g = 2.06), and even superior pooled effect sizes compared to cognitive and behavioral interventions at post-treatment and at follow-up (Hedges’ g 0.69 and 0.37 respectively) [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with others demonstrating the clinical efficacy of MCT [ 2 , 6 , 16 , 22 ]. A recent meta-analysis integrating data of 15 trials demonstrated large effect sizes of MCT against waitlist condition (Hedges’ g = 2.06), and even superior pooled effect sizes compared to cognitive and behavioral interventions at post-treatment and at follow-up (Hedges’ g 0.69 and 0.37 respectively) [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with others demonstrating the clinical e cacy of MCT (Dammen et al, 2016;Hjemdal et al, 2019;Solem et al, 2019;Wells et al, 2012). A recent meta-analysis integrating data of 15 trials demonstrated large effect sizes of MCT against waitlist condition (Hedges' g = 2.06), and even superior pooled effect sizes compared to cognitive and behavioral interventions at post-treatment and at follow-up (Hedges' g 0.69 and 0.37 respectively) (Normann and Morina, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, many mental and emotional responses exist despite not being functional. For example, rumination probably does not solve problems (Kennair et al, 2017), while discontinuing rumination seems to actually increase adaptive behavior as measured by increased quality of life and improved workforce participation or study activity 3 years after treatment (Solem et al, 2019). Panic disorder exists, but in different countries how patients misinterpret, in a positive feedback loop, bodily sensations of anxiety such that in some Arabic countries they will perceive a Djinn sitting on their chest while in Western countries people may fear a heart attack.…”
Section: Discussionmentioning
confidence: 99%